PERSEPSI KELUARGA PEMULUNG TENTANG NILAI PENDIDIKAN DI KELURAHAN LIMBUNGAN BARU KECAMATAN RUMBAI PESISIR KOTA PEKANBARU PROVINSI RIAU - Vendriyani. N, Hartika; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in the village LimbunganRumbai New Coastal District of the city of Pekanbaru. The purpose of this study was to determine how families view scavengers to education. The study titled "Perception of scavenger families about the value of education in the Village District of New LimbunganRumbai Coastal Pekanbaru City Riau Province". Topics focus of this research is how the perception of scavenger families for children's education. Informants of this research is that there are in the village scavenger New Limbungan. Informants retrieval is done by purposive sampling technique. Informants are numbered 10 people scavengers. The author uses qualitative descriptive method and data analyzed qualitative. Data instrument is observation, interview and documentation. The results showed that there were four children in a family scavenger value is the value of affection, economic value, great family value and social value. In addition to the education of children of scavengers view is influenced due to internal factors (the willingness of children, parents income, parental education), and because of external factors (school fees, the school distance, environmental, and geographic factors).Keywords: Value kids, Perceptions, and Education